Diagnostic performance of adult-based ultrasound risk stratification systems in pediatric thyroid nodules: a systematic review and meta-analysis - Xing, Zhichao; Qiu, Yuxuan; Zhu, Jingqiang; Su, Anping; Wu, Wenshuang (Frontiers in Endocrinology, 2023)
Purpose: Ultrasound (US) is the first choice in the detection of thyroid nodules in pediatric and adult patients. The purpose of this study was to evaluate the diagnostic performance of adult-based US risk stratification systems (RSSs) when applied to the pediatric population. Methods: Medline, Embase and Cochrane Library (CENTRAL) were searched up to March 5, 2023, for studies about the diagnostic performance of adult-based US RSS in pediatric patients. The pooled sensitivity, specificity, positive likelihood ratio (LR), negative LR and diagnostic odds ratio (DOR) were calculated. The summary receiver operating characteristic (SROC) curves and area under the curve (AUC) were also analyzed. Results: The sensitivity was highest in American College of Radiology-Thyroid Imaging Reporting and Data System (ACR-TIRADS) category 4-5 and American Thyroid Association RSS high-intermediate risk (ATA), which was 0.84 [0.79, 0.88] and 0.84 [0.75, 0.90], respectively. The specificity was highest in ACR-TIRADS category 5 and Europe-TIRADS (EU-TIRADS) category 5, which was 0.93 [0.83, 0.97] and 0.93 [0.88, 0.98], respectively. The ACR-TIRADS, ATA, and EU-TIRADS showed moderate diagnostic performance in pediatric thyroid nodule patients. For Korea-TIRADS (K-TRADS) category 5, the summary sensitivity and specificity with a 95% CI were 0.64 [0.40, 0.83] and 0.84 [0.38, 0.99], respectively. Conclusions: In conclusion, the ACR-TIRADS, ATA, and EU-TIRADS have moderate diagnostic performance in pediatric thyroid nodule patients. The diagnostic efficacy of the K-TIRADS was not as high as expected. However, the diagnostic performance of Kwak-TIRADS was uncertain because of the small sample size and small number of studies included. More studies are needed to evaluate these adult-based RSSs in pediatric patients with thyroid nodules. RSS specific for pediatric thyroid nodules and thyroid malignancies were necessary.